Synthesis and lewis acidity of fluorinated triaryl borates. Issue 6 (20th January 2023) - Alharbi, Mashael M.; van Ingen, Yara; Roldan, Alberto; Kaehler, Tanja; Melen, Rebecca L.
Abstract : A series of fluorinated triaryl borates B(OAr F )3 (Ar F = 2-FC6 H4, 3-FC6 H4, 4-FC6 H4, 2, 4-F2 C6 H3, 3, 5-F2 C6 H3, 2, 3, 4-F3 C6 H2, 2, 4, 6-F3 C6 H2, 3, 4, 5-F3 C6 H2 ) have been prepared and isolated from the reactions of the mono-, di-, or tri-fluorophenol with BCl3 . Abstract : A series of fluorinated triaryl borates B(OAr F )3 (Ar F = 2-FC6 H4, 3-FC6 H4, 4-FC6 H4, 2, 4-F2 C6 H3, 3, 5-F2 C6 H3, 2, 3, 4-F3 C6 H2, 2, 4, 6-F3 C6 H2, 3, 4, 5-F3 C6 H2 ) have been prepared and isolated from the reactions of the mono-, di-, or tri-fluorophenol with BCl3 . The Lewis acidity of these borates has been determined by NMR spectroscopic and theoretical methods and compared to their well-established borane counterpart.